Postmarketing Safety of a Levonorgestrel/Ethinyl Estradiol Contraceptive Transdermal Delivery System [A24]. (May 2022) - Kroll, Robin; Chiodo, Joseph; Previtera, Michelle; Korner, Paul; Kaunitz, Andrew M.; Teixeira, Beata
Abstract : INTRODUCTION: TWIRLA is a low-dose contraceptive transdermal delivery system of 120 µg/day levonorgestrel and 30 µg/day ethinyl estradiol (LNG/EE TDS) used in a 28-day cycle. It was approved by the US Food and Drug Administration in February 2020 as a method of contraception for use in women of reproductive potential with a body mass index (BMI) <30 kg/m2. The phase 3 SECURE study showed an acceptable safety profile for the LNG/EE TDS in a clinical trial setting. This assessment provides an update of LNG/EE TDS safety based on real-world postmarketing adverse event reporting. METHODS: Data collected from LNG/EE TDS standard postmarketing reporting during December 2020 through September 2021 were assessed and describe serious adverse events (SAEs) to date, including venous thromboembolism (VTE, an event of special interest), and the number of patients who received replacements in a patch-replacement program. RESULTS: Approximately 14, 600 prescriptions for the LNG/EE TDS were dispensed during this postmarketing period, with additional patches dispensed as samples. No VTEs were reported. Two SAEs (one case each of suicidal ideation and loss of consciousness) were reported; based on spontaneous reporting, no new safety issues were identified. Reports of TDS adhesion issues were rare; only 11 individuals received a replacement over the 10-month period. CONCLUSION: In this assessment of real-world usage of the LNG/EE TDS, SAEs and TDS replacements were infrequent and no VTEs were reported. These findings are consistent with the safety profile reported in the SECURE study, where four patients with VTEs were identified, all in women with a BMI >30 kg/m2.